Synthetic gene frequency maps of man and selective effects of climate - Piazza, A. (1981)
The world distribution of 39 independent gene frequencies in human populations is analyzed by multivariate techniques and synthetic geographic maps. Most genetic variation is associated with longitude, with South Asia showing a tendency to be central. Also latitude and, more particularly, distance from the equator play a significant role in a way that suggests that climatic factors exercise selective pressures, especially for certain genes.